Wykorzystanie funkcji controllingu w realizacji usług publicznych na podstawie badań - Borowiec, Leszek (Controlling Functions in the Process of Public Services Rendering on the Basis of Conducted Survey, 2007)
The article presents the results of the research concerning the use of controlling functions by communities in Poland on the basis of conducted survey. The article covers characteristics of the basic functions of the controlling in the process of public services rendering, i.e. planning, monitoring, control, management of information and directing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 45-58